PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS STEAM PROJECT BASED LEARNING DALAM MENINGKATKAN KOGNITIF SISWA SEKOLAH MENENGAH PERTAMA - Emas Marlina (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This article reviews the literature on module development in mathematics learning. The purpose of this development is to review the literature on the preparation of mathematics learning models for junior high school students using the STEAM Project Based Learning learning model in improving students' cognitive abilities. This development method uses a literature review that discusses the development of teaching material modules by raising cognitive elements in the learning process. This module can be implied in mathematics learning in junior high schools, one of which is in the material of spatial structures with simple building designs (integrating geometry and art concepts). Mathematics learning modules based on STEAM project based learning in junior high schools need to be used and designed to improve students' cognitive abilities by involving four dimensions of knowledge in the development of cognitive psychology consisting of four types of knowledge, namely Factual, Conceptual, Procedural, and Metacognition.